Development of Reaction Motion Training Tools for Children with Hearing-Impaired in Central Java Special School in 2019 - Tarigan, Dea Valencia; Soegiyanto, Soegiyanto; Ciptaning Wahyu, Imam Santosa (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
People with hearing impaired who experience loss of listening ability require physical education which provides opportunities for deaf children to take advantage of physical activities to develop and improve neuromuscular, perceptual, cognitive, and emotional levels. This study used a procedural development model, where the model in this study is descriptive, which is a procedure that outlines the steps that must be followed in producing a product. The research subjects carried out in this study were divided into 2 groups. One group in the trial phase 1 and the second group in the trial phase 2. The results of this study were the results of the validation test by the early-stage material experts got an average percentage of 72.22% good criteria. The results of the validation of the electrical experts got an average percentage of 77.55% good criteria. The results of the second stage of validation by hearing-impaired experts got an average percentage of 90.24% outstanding criteria and the average percentage results by electro experts got 92.5% perfect criteria. The results of the small scale try out of 12 children with hearing-impaired got a percentage score of 64.28%. Category